PEMBENTUKAN ENERGI DALAM TUBUH MANUSIA (keterkaitan ilmu Biologi dan Fisika) - Hasbiyati, Haning (JURNAL BIOSHELL, 2012)
Energy can to inspect from Biology, Physics, and Chemistry. Energy formed alteration process that alteration space is human body. Energy alteration to consist of potential and mechanic energy. Energy inside human body unpermanent appearance but to depend on situation, position, body movement, and surrounding environtment. One of something kinetic energy is a termal energy element to mention temperature. Different temperature from one substance to other formed transmition termal energy to mention a heat through some mechanism is conduction, convection, and evaporation.Key word: energy, human body, and termal.